Body Mass Index in Late Adolescence and Later Life Kidney Outcomes: A Population-Based Cohort Study in Swedish Men - Monika Vitkauskaitė; Ernesta Mačionienė; Rytis Stankevičius; Marius Miglinas; Joachim H. Ix; Mattias Brunström (Kidney Medicine)
Rationale & Objective: The association between body mass index (BMI) and chronic kidney disease (CKD) is well established in middle-aged and older adults. Here, we assess the association of BMI in late adolescence with CKD, kidney failure, and acute kidney injury (AKI) later in life. Study Design, Setting & Participants: Population-based cohort study including data from the Swedish Conscription Database, the National Patient Register, the Cause of Death Register, and Statistics Sweden. Conscripts with no history of diabetes, cardiovascular, kidney, or rheumatic diseases enlisted between 1969 and 1997 were followed until December 31, 2019. Main Outcomes & Exposures: The study examined the impact of BMI on kidney outcomes. The primary outcome was incident chronic kidney disease. Secondary outcomes were stage 5 chronic kidney disease, end-stage kidney disease, and acute kidney injury. Analytical Approach: Patients were stratified into the quintiles of BMI at conscription, and followed until events, death, or censoring, using Cox proportional hazards model, adjusted for baseline systolic and diastolic blood pressure, proteinuria, and socioeconomic factors. Results: In total, 1,321,481 male participants with a mean age of 18.3 years and a mean BMI of 21.6 kg/m2 were followed for an average of 35.6 years, generating a total of 47 million person-years of follow-up. During this period, the incidence of CKD-based on diagnosis codes was 5,590, whereas 2,357 subjects were diagnosed with end-stage kidney disease and 8,023 with AKI, respectively. The risk for CKD was increased for the fourth and fifth highest BMI quintile relative to the lowest (adjusted hazard ratio [aHR] 1.23; 95% confidence interval [CI], 1.13-1.35 for BMI 21.9-23.5 kg/m2; aHR 2.09; 95% CI, 1.93-2.26 for BMI >23.5 kg/m2). Patterns were similar for stage 5 CKD and end-stage kidney disease, whereas the risk for AKI was evident at the third and higher quintiles (aHR 1.14; 95% CI, 1.06-1.23 for BMI 20.7-21.9 kg/m2; aHR 1.31; 95% CI, 1.22-1.41 for BMI 21.9-23.5 kg/m2; and aHR 1.92; 1.79-2.05 for BMI ≥23.5 kg/m2). Limitations: A retrospective observational study of male Swedish adolescents. Conclusions: The findings of this study indicate that, for prevention of kidney disease, the optimal BMI in adolescence with reference to kidney outcomes is likely in the low-normal range. Plain Language Summary: This study investigates the long-term link between body mass index (BMI) during late adolescence and kidney failure and acute kidney injury. It draws from a large, population-based Swedish cohort, tracking over a million young men over decades. The research shows that higher BMI in adolescence is associated with an increased risk of kidney problems as adults, with those in the higher BMI ranges facing a significantly greater chance of developing chronic kidney disease and acute kidney injury. The risk was particularly high for individuals with higher BMI levels. These findings suggest that maintaining a low-normal BMI during adolescence may help prevent kidney-related diseases later in life.